Multicenter survey on emergency nurses’ perception of Numerical Rating Scale reliability at triage time in adult Emergency Department patients - Gianfranco Cervellin; Ivan Comelli; Andrea Bellone; Fabrizio Giostra; Nicoletta Acierno; Michele Mitaritonno; Ciro Paolillo; Fabrizio Mastroianni; Matteo Pistorello; Gianni Rastelli; Giorgio Ricci; Andrea Tenci; et al. (Emergency Care Journal, 2018)
Since pain perception is highly subjective and culturally mediated, its objective evaluation remains difficult. Nevertheless, pain measurement should ideally be a part of the assessment of patients in order to plan adequate pain relief. Several scales have been proposed for pain measurement, being the numerical rating scale (NRS) the most widely used, often at triage time. NRS have demonstrated acceptable reliability and validity, in post-operative medicine and in oncologic pain, but data in the Emergency Departments (EDs) are poor. The aim of this study is to evaluate the Emergency Nurses’ (ENs) perception about the reliability of NRS in the triage process. A questionnaire based on 11 items was designed and subsequently administered to a large number of ENs in several EDs in Northern and Central Italy. 301 questionnaires were filled out and returned. The majority declares using NRS scale to measure pain (item 2, mode = 4, mean = 3.8), and attributing priority code based on NRS value (item 3, mode = 4, mean = 3.4). In general, triage nurses believe that NRS is only indicative and that their judgement matters (item 4, mode = 4, mean = 3.2). The vast majority of triage nurses do believe that the patients will indicate a fake higher NRS value with the aim to get a more urgent code (item 5, mode = 5, mean = 4), while only a small minority expects that patients would underestimate their NRS for fear of penalizing more urgent patients. Very few believe that such scale underestimates the patients’ condition, while the majority is ambivalent about whether such scale overestimates it. In conclusion, NRS confirms to be a potentially valuable tool for pain evaluation at triage time, but many nurses express some doubts on its reliability, and will attribute the triage code mainly basing on their own judgement.